Cost minimization analysis of nasopharyngoscope reprocessing in community practice - Ameen Biadsee; Lauren Crosby; Winsion Chow; Leigh J Sowerby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Reprocessing of nasopharyngoscopes represents a large financial burden to community physicians. The aim of this study was to perform a cost analysis of nasopharyngoscope reprocessing methods at the community level. Methods Electronic surveys were distributed by email to community otolaryngologists. Surveys were comprised of 14 questions assessing clinic size, nasopharyngoscope volume, scope reprocessing method and maintenance. Four manual techniques were evaluated: (1) soak with ortho-phthalaldehyde solution (Cidex-OPA; Advanced Sterilization Products, Johnson and Johnson Inc., Markham, Canada), (2) soak with accelerated hydrogen peroxide solution (Revital-Ox; Steris Canada Inc., Mississauga, Canada), (3) disinfection with chlorine dioxide wipe (Tristel Trio Wipes System; Tristel plc., Cambridgeshire, UK), (4) UV-C light system (UV Smart, Delft, The Netherlands). All costs are reported in CAD, and consumable and capital costs for reprocessing methods were obtained from reported vendor prices. Time costs were derived from manufacturer recommendations, the Ontario Medical Association Physician’s Guide to Uninsured Services, and the Ontario Nurses Association Collective Agreement. Cost analyses determined the most cost-effective reprocessing method in the community setting. Sensitivity analyses assessed the impact of reprocessing volume and labour costs. Results Thirty-six (86%) otolaryngologists responded and answered the survey. The cost per reprocessing event for Cidex-OPA, Revital-Ox, Tristel and UV system were $38.59, $26.47, $30.53, and $22.74 respectively when physicians reprocessed their endoscopes themselves. Sensitivity analyses demonstrated that Revital-Ox was the least costly option in a low volume, however, the UV system remained the most cost effective in higher volumes. The cost per reprocessing event when done by clinic staff was $5.51, $4.42, $11.23 and $6.21 for Cidex-OPA, Revital-Ox, Tristel and the UV system. Conclusions The UV light system appears to be the most cost-effective method in high volumes of reprocessing, and Revital-Ox is cheaper in lower volumes and when performed by clinic staff rather than physicians. It is important to consider the anticipated work volume, shared clinic space and number of co-workers prior to choosing a reprocessing method. Graphical Abstract